Analisis Pelaksanaan Kegiatan Numerasi dengan Metode Matematika Gasing Yang di Kaitkan dengan Permainan Tradisional pada Siswa Kelas 4 SD N 1 Demulih - Ni Kadek Lespita Devi (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to analyze the implementation of the numeracy learning method using the Gasing Mathematics approach which is associated with traditional games for grade 4 students at SD N 1 Demulih. This research uses a qualitative descriptive method to describe the application of Gasing Mathematics in the numeracy learning process. Data was obtained through observation, interviews and documentation. The research results showed that the combination of Gasing Mathematics and traditional games such as poh-pohan, gowak-gowakan, and meyong-meyongan succeeded in creating an interactive, fun, and effective learning environment in improving mathematical understanding. The integration of traditional games with Gasing Mathematics makes it easier for students to overcome numeracy difficulties, increases participation, and motivates them in the learning process. This article plays a role in providing new insights into innovative and contextual mathematics learning strategies, especially in supporting the improvement of numeracy skills in elementary schools.